2010
DOI: 10.1111/j.1365-2850.2009.01509.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigating mental health service user views regarding sexual and relationship issues

Abstract: To date, very few empirical studies exist that investigate sexual and relationship issues and people who experience enduring mental health problems and less attention has been paid to the personal accounts of clients in this respect. The present study, carried out in the UK, involved 30 people who were asked about past and present relationship experiences and elicited hopes and aspirations for future sexual and relationship needs. A semi-structured interview schedule was constructed that specifically addressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
74
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(78 citation statements)
references
References 28 publications
(38 reference statements)
3
74
0
1
Order By: Relevance
“…Approval is a vital step in this process (Volman & Landeen, 2007), because of the common barriers related to boundary and gender concerns (Quinn, Happell, & Browne, 2011b). There is a need to provide nurses with permission to talk about this topic (Magnan et al, 2005;McCann, 2010;Odey, 2009;Wright & Pugnaire-Gros, 2010) and to let them know, that consumers are not only willing to engage, but are in a position where they are waiting for nurses to initiate discussion on the topic (Kelly & Conley, 2004;McCann, 2010).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Approval is a vital step in this process (Volman & Landeen, 2007), because of the common barriers related to boundary and gender concerns (Quinn, Happell, & Browne, 2011b). There is a need to provide nurses with permission to talk about this topic (Magnan et al, 2005;McCann, 2010;Odey, 2009;Wright & Pugnaire-Gros, 2010) and to let them know, that consumers are not only willing to engage, but are in a position where they are waiting for nurses to initiate discussion on the topic (Kelly & Conley, 2004;McCann, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Consumers are willing and able to discuss their sexual health concerns (McCann, 2010), and there is an identified need for mental health nurses to facilitate communication about the sexual health concerns of consumers (Phillips & McCann, 2007). However, little progress has been made in meeting such needs of consumers (Higgins, Barker, & Begley, 2008;Wright & Pugnaire-Gros, 2010).…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…In China, nurses reported that nurses' shortage and lack of resources are significant barriers to address patients' sexual health [55]. Furthermore, lack of support from the institutions [56], lack of privacy [57], work overload and a sense that addressing sexual health is non-nursing job [29] are cited as organizational barriers.…”
Section: Organizational-related Barriersmentioning
confidence: 99%
“…It has been suggested by Earle (2001) that potential perpetrators perceive mental health consumers as easy prey, and that consumers may find it difficult to articulate their abuse, may be less likely to be believed, and may lack the knowledge required to understand when abuse has taken place. Unfortunately, consumers' sexuality is often ignored by mental health professionals and researchers, creating a situation where consumer concerns and needs are overlooked (Earle, 2001;Fortier et al, 2003;171 Katz, 2002;McCann, 2010;Quinn & Browne, 2009;Shield, Fairbrother, & Obmann, 2005;Wong & Mak, 2008;Woolf & Jackson, 1996).…”
mentioning
confidence: 98%